Complementary and Alternative Medicine (CAM) Use among Women of Reproductive Age in the United States - Johnson, Pamela Jo (Womens Health Issues, 2015)
BACKGROUND: The purpose of this study was to examine the prevalence of complementary and alternative medicine (CAM) use, types of CAM used, and reasons for CAM use among reproductive-age women in the United States (US). METHODS: Data are from the 2007 National Health Interview Survey (NHIS). We examined a nationally representative sample of US women ages 18–44 (n=5,764 respondents). Primary outcomes were past year CAM use, reasons for CAM use, and conditions treated with CAM by pregnancy status (currently pregnant, gave birth in past year, neither). Multivariate logistic regression was used to estimate the odds of CAM use by pregnancy status. FINDINGS: Overall, 67% of reproductive-age US women reported using any CAM in the past year. Excluding vitamins, 42% reported using CAM. Significant differences in use of biologic-based (P=0.03) and mind-body therapies (P=0.012) by pregnancy status were found. Back pain (17.1%), neck pain (7.7%), and anxiety (3.7%) were the most commonly reported conditions treated with CAM among reproductive-age women. However, 20% of pregnant and postpartum women used CAM for pregnancy-related reasons, making pregnancy the most common reason for CAM use among pregnant and postpartum women . CONCLUSIONS: CAM use during the childbearing year is prevalent, with one-fifth of currently or recently pregnant women reporting CAM use for pregnancy-related reasons. Policymakers should consider how public resources may be used to support appropriate, effective use of alternative approaches to managing health during pregnancy and postpartum. Providers should be aware of the changing needs and personal health practices of reproductive age women.